PENDAMPINGAN POLA ADAPTASI MASYARAKAT PESISIR TERHADAP KELANGKAAN SUMBER AIR BERSIH DI NEGERI ITAWAKA KABUPATEN MALUKU TENGAH - Latuamury, Bokiraiya; Imlabla, Wilma Nancy; Marasabessy, Husain (Jurnal Abdi Inovatif : Pengabdian kepada Masyarakat, 2024)
The scarcity of clean water sources is a significant problem in many coastal communities, where access to clean water is limited, and water quality is threatened by pollution and climate change. The community service program (PKM) aims to educate coastal communities on adaptation patterns to the scarcity of clean water sources through effective counseling and assistance to increase community resilience. The extension method uses a participatory approach by involving the community in education regarding introducing water filtration media and training in water treatment technology using simple technology. The educational process for coastal communities in Itawaka State regarding the introduction of filtration media originating from local resources and recognizing adaptation techniques for the use of simple technology such as simple and cheap water filtration systems and efficient storage systems can help overcome the scarcity of clean water, as well as maintaining water filtration systems sustainable clean.